FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU DETEKSI DINI KANKER LEHER RAHIM METODE INSPEKSI VISUAL ASAM ASETAT DI PUSKESMAS CANDIROTO KABUPATEN TEMANGGUNG - Flora Theodora Parapat; Henry Setyawan Susanto; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Early detection of cervical cancer by using an Visual Inspection Acetic Acid  is a measures for early detection of cervical cancer with the methods of VIA. Indonesian women's awareness  for the early detection of cervical cancer is still poor. This is evident from the low coverage of early detection of cervical cancer with Visual Inspection Acetic Acid . The coverage ini Central Java  only 1.08% of women aged 30-50 years, Candiroto health centers about 5%. This study aims to analyze relating factors  to the early detection Cervical cancer methods Visual Inspection Acetic Acid in  Candiroto health centre Temanggung. This study is a cross-sectional approach. Analyzed by chi-square test with 95% significance level. This research subject are 100 woman of childbearing age in Candiroto health centre with simple random sampling. The results showed there is a significant association between information (p = 0.01), husband’s support (p = 0.026) friend’s support(p <0.0001) in the  early detection of cervical cancer VIA method  and there is no significant association between age (p = 0.07), education (p = 0.17 ), job (p = 0.51), knowledge (p = 0.36), attitude (p = 0.097), distance (p = 0.1), health worker’s support (0.1) in the  early detection of cervical cancer VIA method, and.  And the result is factors that have significant association in early detection cervical with VIA methods in Candiroto health centre Temanggung is information exposure, husband's support, and friend’s support.